2022
DOI: 10.1530/ec-22-0121
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling in the adrenal glands of rats in various types of experimental hypertension

Abstract: Wnt/β-catenin signaling plays a key role in maintaining homeostasis, which is disturbed in hypertension. Taking into account the lack of literature describing changes in the Wnt/β-catenin pathway in the adrenal glands under conditions of elevated arterial pressure, here we compare the expression of WNT4, WNT10A, β-catenin and GSK-3β in the adrenal glands of hypertensive rats of various etiologies. The studies were carried out on the adrenal glands of rats with spontaneous hypertension (SHR), renal-vascular (2K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…This may be due to dysregulation of the mechanisms of β‐catenin and CacyBP/SIP dependence and protein degradation in a state of elevated blood pressure. Our previous studies showed similar results of the decrease in the content of β‐catenin in the adrenal glands and heart of rats in the same models of arterial hypertension 21,23 . On the other hand, Xiao et al 24 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This may be due to dysregulation of the mechanisms of β‐catenin and CacyBP/SIP dependence and protein degradation in a state of elevated blood pressure. Our previous studies showed similar results of the decrease in the content of β‐catenin in the adrenal glands and heart of rats in the same models of arterial hypertension 21,23 . On the other hand, Xiao et al 24 .…”
Section: Discussionsupporting
confidence: 61%
“…Our previous studies showed similar results of the decrease in the content of β-catenin in the adrenal glands and heart of rats in the same models of arterial hypertension. 21,23 On the other hand, Xiao et al 24 showed upregulated renal β-catenin in two models of hypertension (induced by angiotensin II infusion and nephrectomy) and decrease of the blood pressure due to inhibition of Wnt/β-catenin, which, according to these authors, indicates that overactive Wnt/β-catenin promotes hypertension. In one of our recent studies regarding canonical Wnt signalling, we also observed a marked increase in the intensity of β-catenin immunoreactivity in the kidneys of rats with spontaneous and renovascular hypertension.…”
Section: F I G U R E 5 Expression Of Genes Codingmentioning
confidence: 99%
“…The involvement of the Wnt/β-catenin pathway in numerous biological processes, such as embryogenic development, adult tissue homeostasis, and wound healing, has received a lot of attention recently . According to our findings, patients had higher levels of β-catenin than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al discovered that canonic Wnt/β-catenin signaling was important in mediating cardiac hypertrophy in hypertension. While Kasacka et al’s study found a significant decrease in the expression of the gene encoding β-catenin in systemic hypertension and a significant increase in the expression of the tested gene in hypertensive rats compared to control groups, such a difference in findings could be explained by the study groups’ different species.…”
Section: Discussionmentioning
confidence: 99%